PSIKOLOGI PENDIDIKAN DALAM PENGELOLAAN KELAS ABAD 21 - Trisna Wahyuningsih; Vava Iman Agus Faisal (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to examine the application of educational psychology principles in classroom management in 21st-century learning and its implications for the effectiveness of the learning process. The study used a qualitative approach with descriptive methods. The research procedures included planning, data collection, data analysis, and drawing conclusions. Data collection techniques were carried out through learning observations, interviews with teachers, and documentation studies. Data analysis was carried out systematically through data reduction, data presentation, and verification. The results of the study indicate that the application of educational psychology principles, such as understanding individual differences, learning motivation, reinforcement, and social interaction, contributes to creating a conducive and participatory classroom climate. Effective classroom management encourages active student involvement and supports the development of 21st-century skills, including critical thinking, collaboration, communication, and creativity. These findings emphasize the importance of integrating educational psychology principles as a foundation for classroom management in improving the quality of learning in the modern education era.